Daily Activity of Male Mice (Mus musculus) in Laboratory - Rian Oktiansyah (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
The importance of observing the behavior of mice in the laboratory is additional information to compare with their behavior in nature and an effort to increase the welfare of mice (animal welfare) through alleviating the pain and suffering associated with scientific procedures. This study aims to study the daily activities of male mice in the laboratory. The method used was ad libitum and focal animal sampling. Based on the ad libitum sampling method, the daily activities of male mice in the laboratory were divided into 9 activities, namely locomotion, grooming, eating, foraging, social, exploration, resting, making nests, and drinking. Based on the focal animal sampling method, the main activity carried out by male mice in the laboratory was locomotion.